Equilibrium of resource allocation in local health standardization in China: a cross-sectional survey among provincial level CDCs - Yi-chen JIANG; Yan-qing YANG; Zhuang-zhuang WANG (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To investigate the status quo and associates of resource allocation in local health standardization and to provide evidences for promoting the construction of health standardization and the establishment of relevant technical support system with national and provincial coordination in China. Methods On-site interview and questionnaire survey were conducted among professionals and staff in 31 Centers for Disease Control and Prevention (CDCs) at provincial level and 5 CDCs at sub-provincial level across China during May - October, 2019. The collected data and information were processed and analyzed qualitatively and quantitatively with Excel 2010. ResultsOf the CDCs surveyed, only 4 employed full-time personnel for health standards management; 26 and 11 had senior professionals being selected as members of the National Health Standards Professional Committee and Local Professional Committees on Health Standards; and CDCs of Jiangsu province and Beijing municipality had more senior professionals being selected as members of the national committee. There were relative lack and allocation disequilibrium of senior professionals for local health standardization. In terms of financial resources, only 6 CDCs were supported with special funds or budgets for health standardization management and 8 CDCs had financial support for local health standardization management; in 2018, 17 CDCs obtained funds for research projects on health standardization and the CDC of Jiangsu province was involved in more projects with the funds; the funds for local health standardization research was relatively insufficient, and the fund amount was closely related to regional economic development. Conclusion In China, the resource allocation in local health standardization is imbalanced; more resources are allocated in economically developed regions but less in underdeveloped regions, suggesting that specific policies should be made to improve the situation nationwide.